PENGONTROLAN PEMBATASAN JUMLAH PENUMPANG PADA GERBONG KRL UNTUK PENERAPAN PROTOKOL KESEHATAN COVID 19 BERBASIS MIKROKONTROLER - Syofian, Andi; Yultrisna, Yultrisna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Public places such as KRL transportation facilities are one of the great potential places for the transmission of covid-19. In one KRL carriage only a maximum of 60 passengers are allowed, which is 30% of the normal number to prevent the spread and transmission of Covid-19. Therefore, based on the explanation and reasons above, the writer raises a title of the final project which aims to implement social distancing in KRL (Electric Rail) transportation, namely the Passenger limiting the Number of Passengers in KRL Cars for the Application of the Microcontroller-Based Covid 19 Health Protocol.This tool uses an Infrared sensor as input data to be sent to Arduino. The output produced by the microcontroller, in the form of an up down counter that is displayed on the LCD, when the infared sensor reads that a passenger has entered the relay carriage, it will activate and the water pump will spray disinfectant. If the passenger in the carriage reaches the maximum limit, the DC motor and DFplayer get data from the microcontroller. DFplayer will process audio data and forward it to the Loudspeker as its output to inform that the number of passengers in KRL cars has reached the maximum limit that has been determined in accordance with the Covid-19 health protocol.In addition to being able to count the number of passengers, this limiting device for the number of passengers can also limit the number of passengers according to a predetermined number and automatically close the door when the number of passengers exceeds the maximum limit.Keywords: Infrared Sensor, Microcontroller,Relay, Motor Dc, and DFPlayer